A Semantic Analysis of Polysemy in Conan Gray’s “Wishbone” Album Lyrics - Natalia, Cindy; Handayani, Nurma Dhona (PROJECT (Professional Journal of English Education), 2026)
This study aims to analyze the use of polysemy in the lyrics of Conan Gray’s Wishbone album using a semantic approach. The research focuses on identifying polysemous words, classifying their types based on Asher’s (2011) theory of logical and accidental polysemy, and explaining how contextual meanings shape their interpretation. A qualitative descriptive method was applied, and the data were collected through document analysis of the official lyrics from twelve songs in the album. The findings reveal a total of 66 polysemous words, consisting of 45 logical polysemy cases (68.2%) and 21 accidental polysemy cases (31.8%). The dominance of logical polysemy indicates that Conan Gray predominantly uses systematic meaning extension, whereas accidental polysemy contributes symbolic and emotional complexity. The analysis demonstrates that polysemy plays an essential role in expressing themes of love, heartbreak, identity, and emotional vulnerability in the album. This research provides a linguistic contribution to the study of semantics in contemporary song lyrics and offers pedagogical value in helping EFL/ESL learners understand lexical ambiguity and meaning construction in authentic texts.